South African Job Creation, a Myth or Reality? The Role of Economic Injections as a Solution to the Employment Issues: Array - Habanabakize, Thomas; Dickason, Zandri (Acta Universitatis Danubius. Œconomica, 2021)
The paper investigated the effect of economic injections components (exports, government expenditure and domestic investment) on South African employment growth. The study employed quarterly secondary data for the period 2002-2021. The ARDL, ECM and Granger causality approaches were utilised to determine the long run, short-run and causality relationships amongst variables. The results indicated that the long-run growth in both exports and government expenditure leads to employment growth whilst a rise in domestic investment reduces employment levels. Irrespective of long run results, the domestic investment significantly creates jobs in the short term. Additionally, the study results suggested a bidirectional causality between employment exports and a unidirectional from government spending towards employment. Based on the aforementioned results, the study concluded that economic injections play a crucial role in curbing unemployment growth in South Africa. Therefore, the South African government should induce and strengthen exports oriented policies and increase its spending on production-related activities rather than consumption expenditure.